1999
DOI: 10.1897/1551-5028(1999)018<0950:dtoccm>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Toxicity of Copper Chloride, Methylene Chloride, and 6-Aminonicotinamide to Embryos of the Grass Shrimp Palaemonetes Pugio

Abstract: Abstract-Embryos of estuarine grass shrimpPalaemonetes pugio have demonstrated sensitivity to various solvents and petroleum products, indicating utility for evaluating estuarine contamination. Testing was performed to establish concentration-response curves for methylene chloride, copper chloride, and 6-aminonicotinamide, three known teratogenic chemicals. Two exposure periods were used, 4 d and 12 d, and both periods extended through hatching. The average 4-d LC50 values for methylene chloride, copper chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…For instance, copper concentrations found to be lethally toxic to the shrimp Callianassa australiensis were between 1.0 and 2.0 mg L À1 for short (4 d) exposure (Rayburn and Fisher 1999) and 1 order of magnitude lower (0.1 mg L À1 ) for long (14 d) exposure (Ahsanullah et al 2018). Besides the environmental relevance of this response, spatial avoidance can be integrated in different endpoints used in other studies with crustaceans.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, copper concentrations found to be lethally toxic to the shrimp Callianassa australiensis were between 1.0 and 2.0 mg L À1 for short (4 d) exposure (Rayburn and Fisher 1999) and 1 order of magnitude lower (0.1 mg L À1 ) for long (14 d) exposure (Ahsanullah et al 2018). Besides the environmental relevance of this response, spatial avoidance can be integrated in different endpoints used in other studies with crustaceans.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to a much higher concentration of copper (3 mg Cu Total /L) was reported to reduce hatching success of P. pugio embryos in vitro (Rayburn and Fisher, 1999). Furthermore, copperinduced decreases in hatching success rates have been observed in other crustaceans such as crabs (Callinectes sapidus [Lee et al, 1996]) and mysid shrimp (Praunus flexuosus [Garnacho et al, 2001]).…”
Section: Nominal Treatment [Cu] In Tissuementioning
confidence: 99%
“…Although this amount of time appears to be trivial relative to the length of the shrimp's life cycle, it results in a 12-18% increase in the duration of the larval stage, which may be the most vulnerable to predation due to its planktonic nature (Anderson, 1985). Additional examples of copper-induced delayed development in aquatic invertebrates include delayed embryonic development in P. pugio (Rayburn and Fisher, 1999), slower larval development in Metapenaeus ensis (shrimp; Wong et al, 1995) and Watersipora subtorquata (bryozoan; Ng and Keough, 2003), and delayed sexual maturation in Tigriopus japonicus (copepod; D' Agostino and Finney, 1974). Delays in metamorphosis may result in a greater impact of predators on population growth in areas where copper concentrations are elevated.…”
Section: Nominal Treatment [Cu] In Tissuementioning
confidence: 99%
“…Embryos were removed from female grass shrimp by a cut at the stem attaching them to females following the procedures described by Rayburn and Fisher (1999). Embryos, approximately 400, from a single large female were used for each stage specific exposure with a particular test chemical.…”
Section: Hatching and Survival Testsmentioning
confidence: 99%
“…At the end of embryonic development the stage 10 embryos hatch into a free swimming zoea stage which captures its own food. Grass shrimp, including embryos, larvae, juveniles and adult stages, have been used to determine the effects of environmental contaminants in both field studies and laboratory bioassays (Finley et al, 1998;Fisher and Foss, 1993;Fulton, Daugomah, Beardon, & Scott, 1998;Lee, Kim, Maruya, Steinert, & Oshima, 2000;Rayburn & Fisher, 1999;Rayburn, Glas, Foss, & Fisher, 1996). Glas, Courtney, Rayburn, and Fisher (1997) showed that late stage grass shrimp embryos were more permeable than early stages to certain toxicants.…”
Section: Introductionmentioning
confidence: 99%